2020
DOI: 10.1186/s12885-020-07632-4
|View full text |Cite
|
Sign up to set email alerts
|

TRIM study protocol - a prospective randomized multicenter Trial to assess the Role of Imaging during follow-up after radical surgery of stage IIB-C and III cutaneous malignant Melanoma

Abstract: Background The incidence of cutaneous malignant melanoma (CMM) is increasing worldwide. In Sweden, over 4600 cases were diagnosed in 2018. The prognosis after radical surgery varies considerably with tumor stage. In recent years, new treatment options have become available for metastatic CMM. Early onset of treatment seems to improve outcome, which suggests that early detection of recurrent disease should be beneficial. Consequently, in several countries imaging is a part of the routine follow-up program after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Another study from 2 major Danish centers found that routine FDG PET-CT scans detected occult distant recurrence in 13.8% of patients within the first 17.7 months . However, randomized studies of the survival effect of routine imaging are needed, and results from the ongoing Swedish TRIM trial (Trial to Assess the Role of Imaging During Follow-up After Radical Surgery of Stage IIB-C and III Cutaneous Malignant Melanoma) are awaited …”
Section: Discussionmentioning
confidence: 99%
“…Another study from 2 major Danish centers found that routine FDG PET-CT scans detected occult distant recurrence in 13.8% of patients within the first 17.7 months . However, randomized studies of the survival effect of routine imaging are needed, and results from the ongoing Swedish TRIM trial (Trial to Assess the Role of Imaging During Follow-up After Radical Surgery of Stage IIB-C and III Cutaneous Malignant Melanoma) are awaited …”
Section: Discussionmentioning
confidence: 99%
“…The study protocol for the TRIM study has previously been described in detail [ 14 ]. The main inclusion criterion is radical surgery for stage IIB-C or stage III cutaneous melanoma.…”
Section: Methodsmentioning
confidence: 99%
“…Though the risk of selection bias is minimal when all patients are enrolled in a uniform surveillance protocol such as ours, and lead-time and length bias can be addressed statistically 33 , the effect of surveillance with routine imaging on survival should be investigated in a randomized controlled setting. The results of the ongoing Swedish TRIM-trial 34 are awaited.…”
Section: The Effect Of Routine Imaging On Survivalmentioning
confidence: 99%